ParentCoach: co-designing a chatbot to support first-time parents - Meoli, Leina (Department of Computer Science, 2025)
Recent advancements in chatbot technology have led to their widespread application across various sectors worldwide. Still, significant challenges remain in their effective design and implementation for healthcare in the diverse, multilingual socio-economic contexts in South Africa. These challenges include limited internet connectivity and the need for multilingual support. This dissertation explores the co-design of a chatbot to support first-time parents' informational needs in an urban South African context by drawing on the perspectives of clinicians and parents using an exploratory and co-design approach. I conducted one-on-one interviews with five clinicians to understand their perspectives on parental support needs and exploratory workshops with ten parents to gather insights on their learning challenges and experiences and their informational needs. My analysis of findings emphasizes the importance of designing with empathy to support vulnerable parents, ensuring chatbots complement healthcare professionals, building clinician trust through credible sources and endorsement by reputable healthcare institutions, and enabling repeated access to information to aid parents' information retention. I then conducted two sets of co-design workshops with 21 parents that gave insight into parents' preferences regarding chatbot design modalities and uncovered constraints for our design. These activities underscored the necessity of preparing communities to co-design unfamiliar technologies since most participants were engaging with chatbots for the first time. Despite this unfamiliarity, participants demonstrated an openness to adopt chatbots for parenting support. Some key design contributions from co-design were to supplement multilingual support with English content and integrate simple language with medical terminology to enhance parents' understanding, enable user-initiated chatbot interactions, and offer customizable features for community inclusivity. Though we set out to co-design a chatbot to support first-time parents, I did not end up building one due to various contextual constraints. The prototype is a ``pseudo-chatbot'', a question-andanswer informational resource presented in a chat-like user interface with search and menus for content exploration that we evaluated in a two-week pilot feasibility trial. The results of the trial demonstrated that familiar social messaging interfaces and robust menu designs enhance usability, even without fully interactive chatbot features, and highlighted the importance of aligning chatbot content with parents' priorities to promote engagement.